Identifikasi Dan Uji Postulat Koch Agensia Penyebab Penyakit Bakteri Pada Ikan Lele (Clarias gariepinus) yang Berasal dari Demak - Wijayanti, Aulia Resty; -, Sarjito; Prayitno, Slamet Budi (Journal of Aquaculture Management and Technology, 2013)
The aim of the research was to find out the clinical sign of the catfish sample that has been infected by the bacteria and to find out the causative agent bacteria diseases of Clarias gariepinus from Demak. The fish sample collection used purposive random sampling method. The observation of clinical sign was implemented toward ten catfish samples. The isolation of bacteria from moribund fish surface and kidney of catfish was conducted by streaking method on NA and GSP media. Based on the characteristic of morphology (colour, form of colony), it was obtained five isolate from eleven isolates of bacteria for the next test. The test of postulat koch toward five isolates of ten test fish and characterized them to causative agent bacterial through morphological and biochemical characterization. The result of the research showed that the clinical sign were detected irregular swimming, balance disorders, fish stand still at the bottom of the aquarium, the fish limp, injury/red blisters at the injection site, a pale body color, porous on tails, fins and antennas. The test results of postulates koch obtained that the five isolates (D7, D10, D12, D14, D16) were capable of causing pain on test fish. Based on the postulate test also showed only two isolates (D7 and D12) were caused mortality of 30% of the test fish. The results of the morphological and biochemical characterization found that the five agents causing disease in fish from Demak were abbreviated namely of Pseudomonas plecoglossicida, Flavobacterium sp., Edwardsiella ictaluri, Aeromonas caviae and Aeromonas caviae, respectively.